Intra-Appendiceal Migration of a Copper Intrauterine Device: Case Report and Literature Review - Melo, Stefany Camily Santos; Silva Neto, Rubem Alves da (Brazilian Journal of Case Reports, 2026)
Extrauterine migration of intrauterine devices is rare, with an estimated incidence between 0.1% and 0.3%, and intra-appendiceal location represents an exceptional finding. We report the case of a 32-year-old patient who, after postpartum insertion of a copper intrauterine device, presented with pelvic pain and absence of retrieval strings on gynecological examination. Initial ultrasonography and magnetic resonance imaging did not localize the device, which was identified only three years later by plain abdominal radiography and confirmed by computed tomography, demonstrating migration to the appendix. The patient underwent videolaparoscopic appendectomy with complete removal of the device and had a favorable postoperative course. A systematic literature review was associated with the case report, identifying 17 patients described in 14 publications. Ages ranged from 21 to 44 years, with exclusive involvement of copper intrauterine devices. Most patients presented with abdominal pain, while a significant proportion were diagnosed incidentally. The interval between insertion and detection varied widely, reaching up to 12 years. Plain radiography was the most frequently used initial examination, while computed tomography confirmed the diagnosis in nearly all cases. Videolaparoscopic appendectomy was the predominant approach, associated with adequate recovery and a low complication rate. Intra-appendiceal migration should be considered in cases of non-visualization of intrauterine device strings or nonspecific abdominal symptoms. Immediate radiological investigation, initiated with plain radiography and complemented by computed tomography when necessary, is essential to avoid diagnostic delays. The laparoscopic approach remains a safe and effective treatment.